Application of Nanoparticle Technologies in the Combat against Anti-Microbial Resistance - Kumar, Mayur (Pharmaceutics, 2018)
Anti-microbial resistance is a growing problem that has impacted the world and brought about the beginning of the end for the old generation of antibiotics. Increasingly, more antibiotics are being prescribed unnecessarily and this reckless practice has resulted in increased resistance towards these drugs, rendering them useless against infection. Nanotechnology presents a potential answer to anti-microbial resistance, which could stimulate innovation and create a new generation of antibiotic treatments for future medicines. Preserving existing antibiotic activity through novel formulation into or onto nanotechnologies can increase clinical longevity of action against infection. Additionally, the unique physiochemical properties of nanoparticles can provide new anti-bacterial modes of action which can also be explored. Simply concentrating on antibiotic prescribing habits will not resolve the issue but rather mitigate it. Thus, new scientific approaches through the development of novel antibiotics and formulations is required in order to employ a new generation of therapies to combat anti-microbial resistance.